2019
DOI: 10.7441/joc.219.03.07
|View full text |Cite
|
Sign up to set email alerts
|

Determining Probabilities for a Commercial Risk Model of Czech Exports to China with Respect to Cultural Differences and in Financial Management

Abstract: Certain risks associated with particular human activities cannot be eliminated, with commercial risks representing factors of business success or failure. In the current turbulent environment, proper risk assessment and management is of utmost importance in maintaining competitiveness. The aim of this paper is to present the output of our research which focused on the assessment of commercial risk faced by exporters to China, specifically, determining the probabilities for commercial risk model management. Alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…This knowledge helps decline lack of success. Furthermore, Polak (2019) states that it is important to understand cultural differences to be effective on international market and minimise risks of company failure. His study was made on Czech companies exporting products to China.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge helps decline lack of success. Furthermore, Polak (2019) states that it is important to understand cultural differences to be effective on international market and minimise risks of company failure. His study was made on Czech companies exporting products to China.…”
Section: Discussionmentioning
confidence: 99%
“…Lazaroiu et al (2018) proposed measures to maintain data confidentiality to ensure the General Data Protection Regulation. In researches of risk issues, there are quite popular statistical methods of risk assessment (Hudakova et al, 2018), panel cointegration and causality analysis (Bilan et al, 2020), system dynamics (Jin, 2019), probabilistic methods (Polak, 2019), econometric methods (Bilan et al, 2019d;Mura et al, 2018). Hudáková and Dvorský (2018) proposed assessing the risks in dependence on the rate of implementing the risk management process in the SMEs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the basis of the results, the author concluded that mixed fuzzy expert system and regression displays higher prediction accuracy. Many other researchers, such as Sidehabi et al (2016) and Polak (2019), used the Adaptive Spline Threshold Autoregression (ASTAR) statistical method, and created a commercial risk assessment model specifically for Czech companies that export goods and technologies to China in order to help them determine future export volumes to the PRC.…”
Section: Literature Researchmentioning
confidence: 99%